Dynamic agenda setting - Ying Chen; Hülya Eraslan (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
A party can address only a limited number of issues when in power. What issues to address - the party's agenda - has dynamic implications because it affects what issues will be addressed in the future. We analyze a model in which the incumbent in each period addresses one issue among several issues and the remaining issues roll over to the next period. We identify strategic manipulations in the forms of waiting for the moment, seizing the moment, steering, and preemption depending on how power fluctuates. We discuss efficiency implications of these strategic manipulations.
Keywords: C78; D72; D78; 330; agenda setting; multi-issue bargaining; waiting for the moment; seizing the moment; steering; preemption